Bioinspired Hybrid White Light-Emitting Diodes - Weber, Michael; Niklaus, Lukas; Pröschel, Marlene; Brana Coto, Pedro; Sonnewald, Uwe; Costa Riquelme, Rubén Dario (Advanced Materials, 2015)
The first bioinspired hybrid white-light-emitting diodes (bio-HLEDs) featuring protein cascade coatings are presented. For easy fabrication a new strategy to stabilize proteins in rubber-like material was developed. The synergy between the excellent features of fluorescent proteins and the easily processed rubber produces bio-HLEDs with less than 10% loss in luminous efficiency over 100 hours.

Controlling the Chromaticity of Small-Molecule Light-Emitting Electrochemical Cells Based on TIPS-Pentacene - Weber, Michael; Adam, Matthias; Tykwinski, Rik; Costa, Ruben Dario (Advanced Functional Materials, 2015)
This work demonstrates a novel proof-of-concept to implement pentacene derivatives as emitters for the third generation of light-emitting electrochemical cells based on small-molecules (SM-LECs). Here, a straightforward procedure is shown to control the chromaticity of pentacene-based lighting devices by means of a photoinduced cycloaddition process of the 6,13-bis(triisopropylsilylethynyl) (TIPS)-pentacene that leads to the formation of anthracene-core dimeric species featuring a high-energy emission. Without using the procedure, SM-LECs featuring deep-red emission with Commission Internationale d'Eclairage (CIE) coordinates of x = 0.69/y = 0.31 and irradiance of 0.4 extgreekmW cm-2 are achieved. After a careful optimization of the cycloaddition process, warm white devices with CIE coordinates of x = 0.36/y = 0.38 and luminances of 10 cd m-2 are realized. Here, the mechanism of the device is explained as a host–guest system, in which the dimeric species acts as the high-energy band gap host and the low-energy bandgap TIPS-pentacene is the guest. To the best of the knowledge, this work shows the first warm white SM-LECs. Since this work is based on the archetypal TIPS-pentacene and the photoinduced cycloaddition process is well-knownfor any pentacenes, this proof-of-concept could open a new way to use these compounds for developing white lighting sources.
EAM Import::2019-03-13

Electroluminescence: From White to Red: Electric-Field Dependent Chromaticity of Light-Emitting Electrochemical Cells based on Archetypal Porphyrins (Adv. Funct. Mater. 37/2016) - Weber, Michael; Wittmann, Judith; Burger, Alexandra; Malcioglu, Osman; Segarra-Martí, Javier; Hirsch, Andreas; Coto, Pedro B.; Bockstedte, Michel Georg; Costa, Ruben Dario (Advanced Functional Materials, 2016)
CRIS-Team Scopus Importer:2023-03-07
Keywords: collinear and vicinal regioisomers; electric-field dependent chromaticity; light-emitting electrochemical cells; tetraphenyl porphyrin; thin-film white-emitting sources

From White to Red: Electric-Field Dependent Chromaticity of Light-Emitting Electrochemical Cells based on Archetypal Porphyrins - Weber, Michael; Wittmann, Judith; Burger, Alexandra; Malcioglu, Osman; Segarra-Marti, Javier; Hirsch, Andreas; Coto, Pedro B.; Bockstedte, Michel; Costa, Ruben D. (Advanced Functional Materials, 2016)
The differences in the electroluminescence (EL) of red-emitting free-base (H2TPP) and Zn-metalated (ZnTPP) archetypal porphyrins are rationalized in light-emitting electrochemical cells by means of an electric-field dependent effect, leading to whitish and reddish devices, respectively. Although H2TPP shows superior electrochemical and photophysical features compared to ZnTPP, devices prepared with ZnTPP surprisingly stand out with a deep-red EL similar to its photoluminescence (PL), while H2TPP devices feature unexpected whitish EL. Standard arguments such as degradation, device architecture, device mechanism, and changes in the nature of the emitting excited states are discarded. Based on electrochemical impedance spectroscopy and first-principles electronic structure methods, we provide evidence that the EL originates from two H2TPP regioisomers, in which the inner ring H atoms are placed in collinear and vicinal configurations. The combination of their optical features provides an explanation for both the high- and low-energy EL features. Here, the emitting excited state nature is ascribed to the Q bands, since the Soret excited states remain high in energy. This contrasts to what is traditionally postulated in reports focused on H2TPP lighting devices. Hence, this work provides a new explanation for the nature of the high-energy EL band of H2TPP that might inspire future works focused on white-emitting molecular-based devices.
Keywords: collinear and vicinal regioisomers; electric-field dependent chromaticity; light-emitting electrochemical cells; tetraphenyl porphyrin; thin-film white-emitting sources

Light-Emitting Electrochemical Cells Based on Hybrid Lead Halide Perovskite Nanoparticles - Aygueler, Meltem F.; Weber, Michael; Puscher, Bianka; Medina, Dana D.; Docampo, Pablo; Costa, Ruben Dario (Journal of Physical Chemistry C, 2015)
Methylammonium lead bromide (MAPbBr3) perovskite nanoparticles (NPs) have been recently proposed as a new material for light-emitting diodes, as well as a new paradigm to elucidate the operational mechanism in perovskite solar cells. Here, we have expanded the synthesis concept to fabricate NPs based on formamidinium lead bromide (FAPbBr3). Importantly, we have demonstrated that the photophysical features of this novel material can be easily tuned by exchanging the organic cation, achieving lower radiative bimolecular recombination rate for FAPbBr3 NPs. Additionally, we report for the first time light-emitting electrochemical cells (LECs) based on perovskite NPs by an easily up-scalable spray-coating technique. Stable luminance of 1–2 cd/m2 at low driving currents was achieved for both types of materials. Overall, this work opens a new avenue of research into the field of organic–inorganic metal halide nanoparticles bearing different alkyl ammonium groups and their application in the developing field of thin-film lighting devices.
EAM Import::2019-03-12

Rationalizing Fabrication and Design Toward Highly Efficient and Stable Blue Light-Emitting Electrochemical Cells Based on NHC Copper(I) Complexes - Weber, Michael; Fresta, Elisa; Elie, Margaux; Miehlich, Matthias; Renaud, Jean-Luc; Meyer, Karsten; Gaillard, Sylvain; Costa, Ruben Dario (Advanced Functional Materials, 2018)
Recently, the use of a new family of electroluminescent copper(I) complexes—i.e., the archetypal [Cu(IPr)(3-Medpa)][PF6] complex; IPr: 1,3-bis-(2,6-di-iso-propylphenyl)imidazole-2-ylidene; 3-Medpa: 2,2′-bis-(3-methylpyridyl)amine—has led to blue light-emitting electrochemical cells (LECs) featuring luminances of 20 cd m−2, stabilities of 4 mJ, and efficiencies of 0.17 cd A−1. Herein, this study rationalizes how to enhance these figures-of-merit optimizing both device fabrication and design. On one hand, a comprehensive spectroscopic and electrochemical study reveals the degradation of this novel emitter in common solvents used for LEC fabrication, as well as the impact on the photoluminescence features of thin-films. On the other hand, spectro-electrochemical and electrochemical impedance spectroscopy assays suggest that the device performance is strongly limited by the irreversible formation of oxidized species that mainly act as carrier trappers and luminance quenchers. Based on all of the aforementioned, device optimization was realized using ionic additives and a hole transporter either as a host–guest or as a multilayered architecture approach to decouple hole/electron injection. The latter significantly enhances the LEC performance, reaching luminances of 160 cd m−2, stabilities of 32.7 mJ, and efficiencies of 1.2 cd A−1. Overall, this work highlights the need of optimizing both device fabrication and design toward highly efficient and stable LECs based on cationic copper(I) complexes.
CRIS-Team Scopus Importer:2020-09-14
Keywords: blue electroluminescence; copper(I) complexes; light-emitting electrochemical cells; multi-layered device design; redox stability

White Light-Emitting Electrochemical Cells Based on Deep-Red Cu(I) Complexes - Fresta, Elisa; Weber, Michael; Fernandez-Cestau, Julio; Costa, Ruben Dario (Advanced Optical Materials, 2019)
The synthesis and characterization, as well as photoluminescent and electrochemical features of a series of ionic copper(I) complexes-, i.e., [Cu((NN)-N-<^>)((PP)-P-<^>)](+), where (NN)-N-<^> is 4,4 '-diethylester-2,2 '-biquinoline (dcbq) and (PP)-P-<^> is bis-triphenylphosphine, bis[2-(diphenylphosphino)phenyl)ether] (POP), or 4,5-bis(diphenylphosphino)-9,9-dimethylxanthene (Xantphos)-are reported along with their application to achieve both deep-red and white light-emitting electrochemical cells (LECs). In short, the first deep-red Cu(I)-based LECs featuring high irradiances (approximate to 100 mu W cm(-2)) and excellent color stability (x/y CIE color coordinates of 0.66/0.32) over days are reported. This is achieved by comparing the electroluminescent behavior of this series of complexes with respect to the irradiance and stability, as well as the impact of introducing supporting electrolytes on the device performance. This is rationalized using spectroscopic and electrochemical studies. Finally, the first white-emitting LEC is manufactured with red-emitting copper(I) complexes, achieving x/y CIE color coordinates of 0.31/0.32 and a high color rendering index of 92.
CRIS-Team WoS Importer:2019-10-04